Obtenção de inseticida e fungicida contra formigas cortadeiras e seu fungo simbionte em Myracrodruon urundeuva e de complexos de coordenação com metais de compostos ativos para controle desta praga - Sarria, André Lúcio Franceschini (Universidade Federal de São Carlos, 2012)
Insects are the major competitors for food in relation to humans. Ants ("sauvas" and "quenquéns") are the major pests of several culture and in reforestation areas in Brazil represent more than 75% of the time and financial expenditure in the control of forest pests and obviously limit the full development of agriculture and forestry. The technology involved in the search for pesticides for the control of pests is in the frontiers of science, which involves different aspects of multidisciplinary and can contribute greatly to the agriculture advancement. One of these aspects is related to natural products, where new molecules isolated from plants can serve as prototypes for new insecticides. The aim of this study was the phytochemical study of Myracrodruon urundeuva in order to search for compounds with insecticidal activity and the synthesis of metal complexes of copper with molecules that present biological activity. The phytochemical study led to the isolation and structural identification/caracterization of 34 secondary metabolites, being seven unique and among them, are the dimeric chalcones, only identified in two species of Anacardiaceae. 31 compounds were synthesized: eight of them have the ligands obtained by Mannich reaction with 2-hydroxy-1,4-naphthoquinone; eight complexes from these ligands; two iminic derived from the flavonoid naringine and naringenine; two complex from these ligands; four complexes of the type Cu(FLAV)2 and seven complexes of the type Cu(X)(FLAV) where X is 2,2´-Bipyridine our 1,10´- Phenanthroline. The extracts of M. urundeuva, isolated compounds and metal complexes were tested in nests of Atta sexdens rubropilosa (test of toxicity by ingestion), enzyme inhibition in AChE and fungicide test in ants symbiotic fungus (Leucoagaricus gongylophorus) withsignificative results.
Obtainment of insecticide and fungicide against leaf cutting ants and their symbiotic fungi from myracrodruon urundeuva and of coordination complex of metals with bioactive compounds for the control of this plague.
Keywords: Química orgânica; Produtos naturais; Myracrodruon urundeuva; Complexos metálicos; Fungo simbionte; Formigas cortadeiras; CIENCIAS EXATAS E DA TERRA::QUIMICA